Influence of genetic background and oxidative stress response on risk of mandibular osteoradionecrosis after radiotherapy of head and neck cancer. Issue 3 (26th May 2015) - Danielsson, Daniel; Brehwens, Karl; Halle, Martin; Marczyk, Michal; Sollazzo, Alice; Polanska, Joanna; Munck–Wikland, Eva; Wojcik, Andrzej; Haghdoost, Siamak
Abstract: Background: Osteoradionecrosis (ORN) of the mandible is a severe complication of head and neck radiotherapy (RT) treatment, where the impact of individual radiosensitivity has been a suggested explanation. Methods: A cohort of patients with stage II/III ORN was compared to matched controls. Blood was collected and irradiated in vitro to study the capacity to handle radiation‐induced oxidative stress. Patients were also genotyped for 8 single‐nucleotide polymorphisms (SNPs) in genes involved in the oxidative stress response. Results: A difference in 8‐oxo‐7, 8‐dihydro‐2′‐deoxyguanosine (8‐oxo‐dG) levels was found between the patient cohorts ( p = 0.01). The SNP rs1695 in glutathione s‐transferase p1 (GSTP1) was also found to be more frequent in the patients with ORN ( p = .02). Multivariate analysis of the clinical and biological factors revealed concomitant brachytherapy plus the 2 biomarkers to be significant factors which influense risk of mandibular osteoradionecrosis after radiotherapy of head and neck cancer. Conclusion: The current study indicates that oxidative stress response contributes to individual radiosensitivity and healthy tissue damage caused by RT and may be predicted by biomarker analysis. © 2015 Wiley Periodicals, Inc. Head Neck 38: 387–393, 2016